The chemical mediation of delayed hypersensitivity skin reactions. IV. Activation of chemotactic factor precursor by a trypsin-like protease in guinea pig plasma. - Kawaguchi, T. (1984)
A single-chain precursor protein for macrophage chemotactic factor was previously reported (Ueda et al, Am J Pathol, 1982, 108:291-298). Apparent chemotactic activity was spontaneously generated in the precursor fraction during a long period of incubation, correlating with the cleavage of the precursor molecule into a two-chain protein. Generation and the limited proteolysis were both inhibited by phenylmethylsulfonyl fluoride (PMSF), a serine protease inhibitor, suggesting the presence and the role of a serine protease in the fraction. A serine protease was actually activated and separated from the precursor fraction with a benzamidine-conjugated cellulose affinity column. The protease was heat-labile, and the substantial molecular weight was 20,000 by gel filtration on a Sephadex G-75 column and 23,000 by SDS-polyacrylamide gel electrophoresis. It hydrolyzed [3H-acetyl casein and also fluorogenic synthetic substrates, butyloxycarbonylphenylalanylserylarginine methylcoumarylamide and butyloxycarbonylisoleucylglutamylglycylarginine methylcuomarylamide, and was inhibited by diisopropylfluorophosphate, PMSF, trasylol, soybean trypsin inhibitor, and tosyllysine chloromethylketone, but not by tosylphenylalanine chloromethylketone, chymostatin, p-chloromercuricbenzoate or ethylenediaminetetraacetate. By incubation of the precursor with the protease, rapid generation of chemotactic activity for macrophages was observed. The fact that the chemotactic factor newly generated in vitro was identical with a macrophage chemotactic factor previously separated from extract of delayed type hypersensitivity skin sites immunologically and physicochemically suggested an essential role of the protease in macrophage chemotactic factor generation in the delayed hypersensitivity skin reaction.